2006
DOI: 10.1111/j.1365-313x.2005.02640.x
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the alternative pathways of the Arabidopsis respiratory chain by nitrogen supply: opposing effects of ammonium and nitrate

Abstract: SummaryThe mitochondrial oxidative phosphorylation system in plants possesses a variety of alternative pathways that decrease respiratory ATP production. These alternative pathways are mediated by three classes of bypass proteins: the type II NAD(P)H dehydrogenases (which circumvent complex I of the electron transport chain), the alternative oxidases (AOXs; which circumvent complexes III and IV) and the uncoupling proteins (which circumvent ATP synthase). We have monitored the expression of all genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(162 citation statements)
references
References 71 publications
6
153
0
3
Order By: Relevance
“…By consuming reductant that may otherwise increase mitochondrial electron flow independent of ATP demand, one may expect NO3 -assimilation to alleviate reductions in po associated with photoreductant flows. Indeed, Escobar, Geisler & Rasmusson (2006) found that in Arabidopsis thaliana, AOX genes were up-regulated in response to NH4 + nutrition, but down-regulated in response to NO3 -nutrition. Our model predicts that the effect of NH4 + nutrition on P : O ratio, and thus presumably on AOX activity, depends on the ATP : 2e -ratio (pe) in photosynthesis.…”
Section: Implications For Non-phosphorylating Electron Flowmentioning
confidence: 99%
“…By consuming reductant that may otherwise increase mitochondrial electron flow independent of ATP demand, one may expect NO3 -assimilation to alleviate reductions in po associated with photoreductant flows. Indeed, Escobar, Geisler & Rasmusson (2006) found that in Arabidopsis thaliana, AOX genes were up-regulated in response to NH4 + nutrition, but down-regulated in response to NO3 -nutrition. Our model predicts that the effect of NH4 + nutrition on P : O ratio, and thus presumably on AOX activity, depends on the ATP : 2e -ratio (pe) in photosynthesis.…”
Section: Implications For Non-phosphorylating Electron Flowmentioning
confidence: 99%
“…Hence preventing excessive mitochondrial ROS, RNS (reactive nitrogen species, designate NO and other NO-related molecules) production by maintaining carbon pool homeostasis, 19 redox state homeostasis in nitrogen assimilation process. 20,21 and energy state homeostasis during mineral ion uptake.…”
Section: Mechanism Of Aox In Plantsmentioning
confidence: 99%
“…These pathways are not found in other organisms. Interestingly, reorganization of the respiratory bypass pathway in response to nitrogen sources was recently reported (22).…”
Section: Resultsmentioning
confidence: 99%
“…SIZ1 is a SP-RING finger protein that has a DNA-binding (22). These results suggest that alternative respiration-related genes encoding type II NAD(P)H dehydrogenase and several alternative oxidases must be downregulated in the siz1 mutant and that AtSIZ1 can act as a regulator of an alternative respiratory pathway.…”
Section: Introductionmentioning
confidence: 90%